2018
DOI: 10.1177/1474515118772828
|View full text |Cite
|
Sign up to set email alerts
|

Exploring potential biomarkers associated with health-related quality of life in patients with coronary artery disease and heart failure

Abstract: Even after controlling for socio-demographic and clinical risk factors including mental distress symptoms, lower levels of inflammatory biomarkers were associated with worse HRQoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…What is interesting, while multiple studies show that lower IL-6 concentration is correlated with lower cardiovascular risks, it has been reported that decreased levels of inflammatory biomarkers, including hs-CRP and IL-6, were associated with worse health-related quality of life (HRQoL) in patients with CAD and heart failure [ 49 ].…”
Section: Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…What is interesting, while multiple studies show that lower IL-6 concentration is correlated with lower cardiovascular risks, it has been reported that decreased levels of inflammatory biomarkers, including hs-CRP and IL-6, were associated with worse health-related quality of life (HRQoL) in patients with CAD and heart failure [ 49 ].…”
Section: Biomarkersmentioning
confidence: 99%
“…Exploring potential biomarkers associated with health-related quality of life in patients with coronary artery disease and heart failure [49] IL-6, CRP Decreased levels of inflammatory biomarkers, including IL-6 and hs-CRP, were associated with worse health-related quality of life in patients with CAD and heart failure.…”
Section: C-reactive Protein Increase In Acute Myocardial Infarction [34] Crpmentioning
confidence: 99%
“…Similarly, patients with controlled blood pressure have better overall satisfaction with their medications and HRQoL. Patients who had no adverse events and experienced less anxiety and depression had significantly higher overall treatment satisfaction and better HRQoL ( 18 21 ).…”
Section: Introductionmentioning
confidence: 97%
“…Regarding the expected instability of TDP over time, we also wonder whether it may be an expression of maladaptive coping strategies rather than their cause. At any rate, TDP is linked to lowered quality of life in a variety of diseases, e.g., multiple sclerosis [28], coronary artery disease [29], diabetes mellitus [30], and rheumatoid arthritis [31]. NA is held responsible for effectuating the loss in QoL [31].…”
Section: Introductionmentioning
confidence: 99%